Pergeseran Mata Pencaharian Petani - Idrus Hentihu; M Chairul Basrun Umanailo; Darwin Abd Radjak; Andries Lionardo (Mahesa Research Center, 2021)
This paper aims to examine the problem of decreasing agricultural land in Namlea village which has become a new infrastructure development area so that it shifts the function of land out of the agricultural sector. The problem is focused on shifting land use which makes workers in the agricultural sector less and less which affects productivity. This study seeks to identify the impact of urbanization and the diversification actions taken by the community on their agricultural land as an effort to fulfill their daily needs. This study uses a qualitative approach and the number of informants to be interviewed is 15 people who are taken purposively. The research was conducted in Namlea Village, Buru Regency with informants including village officials, BPD members, representatives of community leaders, traditional leaders and religious leaders plus community representatives who are considered to have competencies related to the research objectives. This study uses observation data collection techniques and in-depth interviews. The analytical technique used in this research is qualitative data analysis following the concept given by Miles and Huberman and Spradley. This study concludes that the impact of land conversion results in the limitations of farmers in Namlea Village to access the jobs they have been getting to meet their daily needs and have to do other jobs of course with low pay, all of this is done solely to meet household needs.